The Prevalence and Correlates of Sleep Disturbances and Psychological Symptoms in Healthcare Workers: A Multi-Center Cross-Sectional Study - Sacit İçten; Gülcan Koyuncu (Boğaziçi Tıp Dergisi, 2022)
INTRODUCTION: In this study, we aimed to investigate daytime sleepiness, sleep quality, and psychological symptoms in healthcare workers and to examine the relationship between them. METHODS: This survey study is descriptive and cross-sectional study. The population of the study consists of 1126 healthcare workers in six public health institutions in Istanbul. The study data were collected with a piece of personal information from questioning sociodemographic information, Epworth Sleepiness Scale (ESS), Pittsburgh Sleep Quality Index (PSQI), and the 'Brief Symptom Inventory' that determine the psychological symptom status. The data were analyzed with SPSS 26 package program. RESULTS: Data for 1126 participants who were 22.9% male and with a mean age of 32.10 (+-8.83) years were analyzed. It was determined that there is a large mental health burden on healthcare workers. In general, excessive daytime sleepiness, reduced sleep quality, and psychopathological symptoms were significantly higher than the normal population. They were 19.2%, 52.0%, and 45.7%, respectively. A significant correlation was found between sleep disorders and psychopathological symptoms. It was observed that the ESS and PSQI scores varied according to gender, occupation, and shift status. The difference was statistically significant (p<0.05). There was no difference in daytime sleepiness and sleep quality according to the type of work in those with psychopathology symptoms (p: >0.05). DISCUSSION AND CONCLUSION: The heavy workload and work stress cause sleep problems and psychological symptoms in healthcare workers. To quality and efficient healthcare, working conditions and hours of healthcare workers should be regulated, and training on stress management and sleep hygiene should be provided.